Industrialization and society - Hoselitz, Bert F.; Moore, Wilbert Ellis; International Social Science Council; United Nations Educational, Scientific and Cultural Organization (Mouton : UNESCO, 1963)
The papers presented in this volume were prepared for the North American Conference on Social Implications of Industrialization and Technological Change, which was one of the activities of the Department of Social Sciences of UNESCO.
Proceedings of the Chicago Conference on social implications of industrialization and technical change, 15-22 September, 1960.
Includes bibliographical references.
lje 25/01/2018
Loans
Keywords: Technology and civilization; Industries